Evaluation of Anticancer Potential of Biogenic Copper Oxide Nanoparticles (CuO NPs) against Breast Cancer. (11th April 2022) - Zughaibi, Torki A.; Mirza, Ahmed A.; Suhail, Mohd; Jabir, Nasimudeen R.; Zaidi, Syed Kashif; Wasi, Samina; Zawawi, Ayat; Tabrez, Shams
Abstract : The present study evaluated the anticancer potential of copper oxide nanoparticles (CuO NPs) synthesized from pumpkin seed extract in human breast cancer cell line (MDA-MB-231) using a battery of tests such as MTT [3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide] assay, morphological alteration, reactive oxygen species (ROS) generation, and changes in mitochondrial membrane potential (MMP). The biogenic CuO NPs showed a dose-dependent decline in cell viability with 50% inhibitory concentration (IC50) at 20 μ g/ml. Treatment with an IC50 dose of CuO NPs resulted in considerable morphology changes, such as shrinkage, detachment, membrane blebbing, and deformed shape in MDA-MB-231 cells. We also observed a significant dose-dependent increase in ROS production and MMP modulation due to CuO NP treatment. Overall, CuO NPs showed significant anticancer potential in the breast cancer cell line. However, further validation of our data is required in ex vivo and in vivo models before this nanoformulation could be exploited for the treatment/management of human breast cancer.